أثر تقلبات أسعار المحروقات على الميزان التجاري خلال الفترة 2010-2021 - بطيمي إحسان; كريريش وئام; رمضاني لعلا (جامعة عمار ثليجي الاغواط, 2022)
This study aims to analyze the impact of fluctuations in fuel prices on the trade balance throughout the period 2010-2021We seek to highlight the most important repercussions of volatility and see how much it contributes to the impact on indicators of economic balance.Based on the above we found in this study that the Algerian economy is purely reactionary and this is evident during the period of the decline in fuel prices, which led the latter to a permanent deficit in the trade balance throughout the period of decline